Structural Equation Model: Intention To Use Mobile Banking of Bottom of Pyramid Customer - Dian Kusumaningrum; Dewi Savitri Saraswati; Seprianus Seprianus (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2019)
The economy is shifting into the digital economy and to overcome it, the banking industry competes through innovation and digital strategy. Smartphone-based mobile banking is the key component of the digital strategy with 70% of the banks agree to focus their strategy on mass customer segment (PWC, 2017).The purposes of the study are to identify the predicting factors influencing the intention to use mobile banking and empirically validate a model explaining the behavioral intention to use it, especially on the Bottom of Pyramid (BOP) segment. The model used was Structural Equation Model (SEM) based on Partial Least Square (PLS). The data used for developing the model was based on a survey to 100 BOP households.The results of this study show that the variables that have the highest significant effect on BOP’s customer intention to use mobile banking are involuntary barriers, followed by perceived risk, and attitude. This result can be further used by researchers and mobile banking providers to evaluate the existing mobile banking services to improve its contribution in providing better market penetration and more appropriate financial services for BOP and ultimately financial inclusion in Indonesia.Keywords: Mobile Banking, Intention, Structural Equation Model